Development and Simulation of an Automated Control Algorithm for Insulin Therapy of Hyperglycemic Emergencies in Diabetes - Becerril Rico, Jared (Revista Mexicana de Ingenieria Biomedica, 2020)
This paper describes the development and simulation of an algorithm for the automatic control of insulin infusion, in the glycemic management of patients with diabetic ketoacidosis (CAD) and hyperglycemic hyperosmolar state (EHH). An algorithm was programmed to calculate the requirement insulin for a glycemic decrease of 50 mg/dL/h until reach 250 mg/dL in blood glucose levels, and thus maintaining it at 220 mg/dL until the pathology remission. The software simulation was performed using glycemic records of 10 patients with CAD managed in the Hospital Juárez de México. The results of the simulation showed a lower incidence of hypoglycemia, as well as a lower insu-lin requirement within the treatment, without differences in the average glucose decreases per hour between real and simulated measurements. This software proposes an innovative use of the artificial pancreas in hyperglycemic emergencies, and also implementing the use of insulin sensitivity as a variable for their function. The results show that the algorithm could be able to achieve glycemic management attached to the treatment guidelines, generating lower insulin expenditure and avoiding hypoglycemia during therapy, with a possible application in autonomous biomedical devices.